Balancing 'flexibility' and 'employability': The changing role of general studies in the Finnish and Swedish VET curricula of the 1990s and 2010s. (May 2019) - Nylund, Mattias; Virolainen, Maarit
This article analyses and compares the evolving role of general subjects in the curricula of initial upper secondary vocational education and training (VET) in Finland and Sweden during the 1990s and 2010s. The research illustrates how Bernstein's concept of 'pedagogic code' supports comparative studies on principles guiding changes to curricula and how the role of general studies in VET has been redefined. The findings show that while a principle of 'market relevance' has been central to VET over the decades since the 1990s, it has been subject to varying interpretations. The shifts in interpretations have guided the organisation of VET in these two countries in different directions, including the role of general subjects within the curriculum. On a general level, the countries share some key similarities. Both countries emphasised lifelong learning and a broadening of VET in the 1990s, based on a core principle of 'flexibility'. In the 2010s, the earlier promotion of flexibility and universal access to higher education was superseded by a stronger focus on employability and entrepreneurship in addition to students' command of more specific vocational tasks.